2020
DOI: 10.1039/d0ta01760d
|View full text |Cite
|
Sign up to set email alerts
|

Metal defects in HKUST-1 MOF revealed by vibrational spectroscopy: a combined quantum mechanical and experimental study

Abstract: This paper reports an interpretation of the FTIR and Raman spectra of the HKUST-1 MOF in light of an ab initio theoretical analysis of the vibrational spectra of the framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 72 publications
4
34
0
Order By: Relevance
“…The peak at 811. The analysis is consistent with the literature reports 42,46 , 43,47 , 44,45 , 48 .…”
supporting
confidence: 92%
“…The peak at 811. The analysis is consistent with the literature reports 42,46 , 43,47 , 44,45 , 48 .…”
supporting
confidence: 92%
“…In the HKUST-1 spectrum, the peaks at 745.15 and 829.29 cm −1 are designated as C-H bending vibrations 42,43 . The peak at 811.13 cm −1 is designated as C-H bending in case of Cu(BTC)‱3H The analysis is consistent with the literature reports 42,46 , 43,47 , 44,45 , 48 .…”
supporting
confidence: 89%
“…Besides, FTIR spectra of adsorbed specic probe molecules (e.g., CO, 100,101 CD 3 CN, 80,102 and pyridine 27,81,103 ) have been used to characterize coordinatively unsaturated metal sites, which are associated with missing linker defects. Recently, Gentile et al 104 reported a combination of the FTIR and Raman spectra of the HKUST-1 MOF with an ab initio theoretical analysis of the vibrational spectra to reveal spectroscopic signatures of framework defects.…”
Section: View Article Onlinementioning
confidence: 99%